Application of multi-stage fracturing stimulation based on case study of Chang-7 shale gas formation in Ordos basin - Guang Dong; Yanping Lu; Shuai Dong (Scientific Reports)
Abstract To address the issue of low production output, additional stimulation measures are always adopted.This study analyzes the complex characteristics of the Chang-7 shale gas reservoir in the central Tianhuan Syncline, Ordos Basin. Facing challenges from reservoir heterogeneity, we implemented a multi-stage fracturing pilot in the first horizontal well (DPX) of the Chang-7 reservoir using drillable bridge plug technology and customized fracturing designs based on horizontal well multi-stage stimulation theory and multi-fracture interference mechanisms. Research shows: Fracture parameters (stage count, geometry, length) and operational parameters (perforation scheme, fracturing scale, fluid type, injection rate) designed according to overall reservoir characteristics are significantly affected by heterogeneity during implementation, resulting in substantial variations in operational difficulty and outcomes across stages. Therefore, for reservoirs with strong heterogeneity, stage-specific designs must account for localized features to enhance success rates and production gains.